2019
DOI: 10.1145/3341225
|View full text |Cite
|
Sign up to set email alerts
|

The Supernumerary Hand Illusion in Augmented Reality

Abstract: The classic rubber hand illusion (RHI) experiment studies the sense of embodiment over a fake limb. Distinguished subcomponents of embodiment are ownership (sense of self-attribution of a body), agency (sense of having motor control), and self-location (the spatial experience of being inside a body), and are typically evoked in either reality or virtual reality. In augmented reality (AR), however, visually present real limbs can be augmented with (multiple) fake virtual limbs, which results in a variation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
0
21
1
Order By: Relevance
“…Participants that simultaneously viewed the experimenter's hands from a 1PP and their own hands from a 3PP (using an HMD) while all hands tapped their index fingers, experienced a four-hand illusion (Chen et al, 2018 ). Participants also experienced high levels of ownership and agency over a six-digit virtual hand (Hoyet et al, 2016 ) and a third arm, both in reality (Schaefer et al, 2009 ) and in augmented reality (Rosa et al, 2019 ). In addition, Kishore et al ( 2016 ) found that it is possible to concurrently experience full-body ownership over multiple artificial bodies (two different humanoid robots located in two distinct places and a virtual body represented in immersive VR).…”
Section: Recent Developmentsmentioning
confidence: 99%
“…Participants that simultaneously viewed the experimenter's hands from a 1PP and their own hands from a 3PP (using an HMD) while all hands tapped their index fingers, experienced a four-hand illusion (Chen et al, 2018 ). Participants also experienced high levels of ownership and agency over a six-digit virtual hand (Hoyet et al, 2016 ) and a third arm, both in reality (Schaefer et al, 2009 ) and in augmented reality (Rosa et al, 2019 ). In addition, Kishore et al ( 2016 ) found that it is possible to concurrently experience full-body ownership over multiple artificial bodies (two different humanoid robots located in two distinct places and a virtual body represented in immersive VR).…”
Section: Recent Developmentsmentioning
confidence: 99%
“…The previous sections described experiments where the SoE could be evoked with different levels of body avatarization [32], [113], embodiment perspectives [31], [57], environments [21], [22], [59], display types [1], [12], [59], avatar appearances [59], [76], real body visibility [58], and sensory stimulation [20], [31], [127]. We conclude that, to some extent, the SoE can be elicited independently of the technological context as long as the appropriate stimuli and induction conditions are met.…”
Section: Discussionmentioning
confidence: 99%
“…a sharp knife suddenly falls), studies have shown that participants will attempt to avoid virtual danger in the case where the illusion is successful. This response to danger is reflected in several bodily signals such as the skin conductance response (SCR) and heart rate deceleration (HRD), which can be recorded in both VR and AR [64], [113]. Body ownership illusions have also been correlated with decreases of user body temperature [114] and variations of muscle electrical activity (EMG) [115].…”
Section: Objective Measuresmentioning
confidence: 99%
See 2 more Smart Citations